ANALISIS KEMAMPUAN LITERASI DIGITAL PUSTAKAWAN DI PERPUSTAKAAN SEKOLAH WILAYAH KECAMATAN PONTIANAK SELATAN - Aqilah, Najwa Wahyu (Jurnal Informasi, Perpustakaan, dan Kearsipan (JIPKA), 2023)
Digital literacy must be owned by everyone in the problems caused by the use of new media which is the main media when looking for information. Librarians play a role in providing information to users in schools so that they are required to be able to understand, use media resources and digital information so that they need to have digital literacy skills. The purpose of this research is to describe the digital literacy skills of librarians in the school library in the South Pontianak District. The research method is qualitative with a descriptive approach by interviewing 4 informants. Data collection techniques are interviews, indirect observations, documentation studies. Data analysis techniques are data reduction, data presentation, and conclusion drawing. The data validity test is source triangulation, method triangulation. The results showed that digital literacy skills in the aspect of analysis and evaluate, use, and apply ethical judgment are quite good, while in the aspects of creating and collaborating and sharing, improvement is still needed.